Adaptive Natural Killer Cells Integrate Interleukin-18 during Target-Cell Encounter - Hammer, Quirin; Rückert, Timo; Dunst, Josefine; Romagnani, Chiara (Frontiers in Immunology, 2018)
Human cytomegalovirus (HCMV) infection induces adaptations in the natural killer (NK)-cell compartment. Expanded subsets of adaptive NK cells display potent effector functions against cellular targets, despite their apparent unresponsiveness to stimulation with classical dendritic cell-derived cytokines interleukin (IL)-12 and IL-18. However, it remains unclear whether adaptive NK cells have completely lost their ability to sense inflammation via IL-12 and IL-18 or whether these pro-inflammatory signals can be functionally integrated into defined contexts. Here, we demonstrate that adaptive NKG2C+ NK cells can be costimulated by the presence of pro-inflammatory cytokines during target cell-induced activation. Cytokine costimulation of adaptive NK cells resulted in elevated interferon (IFN)-gamma and tumor necrosis factor (TNF) production, which promoted protein expression of HLA class I and adhesion molecules as well as transcription of genes involved in antigen processing and antiviral states in endothelial bystander cells in vitro. We further show that IL-18 drove costimulation in functional assays and was sufficient for elevated cytokine production in the absence of IL-12. Hence, adaptive NKG2C+ NK cells—although poorly responsive to IL-12 and IL-18 as an isolated stimulus—integrate IL-18 as a costimulatory signal during target-cell encounter.